2001
DOI: 10.1089/108729001317022241
|View full text |Cite
|
Sign up to set email alerts
|

CpG Stimulation of Primary Mouse B Cells Is Blocked by Inhibitory Oligodeoxyribonucleotides at a Site Proximal to NF-κB Activation

Abstract: Bacterial DNA and CpG-oligodeoxyribonucleotides (ODN) are powerful B cell activators, inducing apoptosis protection, cell cycle entry, proliferation, costimulatory molecule expression, immunoglobulin (Ig) and interleukin-6 (IL-6) secretion. However, proximal events in B cell activation by ODN are only partially characterized, including the translocation of NF-kappaB to the nucleus. In this paper, we provide evidence that CpG-ODN-induced cell cycle entry and apoptosis protection are blocked by SN50 or gliotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
84
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 51 publications
7
84
0
1
Order By: Relevance
“…3 and 4). Consistent with these findings, suppressive motifs were recently shown to down-regulate CpG-dependent NF-B and AP-1 induction (17,18). These observations suggest that CpG motifs must continuously signal receptive cells for triggering to persist.…”
Section: Discussionsupporting
confidence: 62%
“…3 and 4). Consistent with these findings, suppressive motifs were recently shown to down-regulate CpG-dependent NF-B and AP-1 induction (17,18). These observations suggest that CpG motifs must continuously signal receptive cells for triggering to persist.…”
Section: Discussionsupporting
confidence: 62%
“…TCR ϭ T cell receptor. activation and may thus limit the pathologic changes caused by CpG-driven immune responses (10,13,25).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which suppressive ODNs inhibit the activity of CpG DNA is a matter of considerable interest. Recent studies suggest that suppressive ODNs interfere with CpG-mediated cell signaling upstream of nuclear factor B activation (11,25). However, suppressive ODNs do not block the cellular uptake of CpG DNA or binding to Toll-like receptor 9 (13).…”
Section: Discussionmentioning
confidence: 99%
“…AO was used in double-stranded form by mixing with an equimolar amount of reverse activating ODN (RAO), heating to 65°C, and cooling slowly to room temperature. 2114L and 2088L are based on 2114 and 2088 (16), but lengthened and made as PO-ODN. LPS from Salmonella minnesota Re595 (Sigma-Aldrich) was dissolved in 0.1% triethylamine and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…Although a number of studies have shown an inhibitory action of viral (12) and vertebrate (13)(14)(15) DNA or specific ODN (12-14, 16 -20), there is no consensus in the literature about the nature of such motifs. The suggestions for inhibitory motifs include GC-rich sequences such as CCGG (12), GC-rich sequences when linked closely to CpG (21), methylated CpG motifs (15), certain G-rich sequences such as GGAGGGG (16,17), and deoxyguanosine (dG) homopolymer (13,14,22). In none of these cases is it known how an inhibitory effect is mediated, and competition for CpG DNA uptake has not always been eliminated as a mechanism.…”
mentioning
confidence: 99%